Monetary credibility vs. voter approval: political institutions and exchange-rate stabilization during crises - Sattler, Thomas; Walter, Stefanie (Economics & politics, 2010)
This paper analyzes how political institutions affect the execution of exchange-rate policy. By focusing on policy-makers' responses to the emergence of speculative pressure on their currencies, we argue that the effect of democratic institutions on exchange-rate stability is likely to be conditioned by the officially announced exchange-rate regime. Officially fixed exchange rates are the main instrument of autocrats to signal commitment to long-term stability. Autocratic governments with strictly fixed exchange rates are thus more likely to defend their exchange rates than autocrats with an intermediate regime because the latter implicitly signal that they care less about monetary stability. In contrast, democrats defend more often in intermediately than in fully fixed official regimes by using a combination of external and internal adjustments, which reduce the negative effects of a devaluation on voters. Our analysis of 189 currency crises between 1975 and 1999 supports this conditional effect.
Gesehen am 08.08.2023